Use of a Fiber Optic Probe for Spectral Measurements and the Continuous Recording of the Turbidity of Growing Microbial Cultures - Robrish, S. A. (1971)
This paper describes the properties and use of a fiber optic probe as an attachment to a spectrophotometer and its use for measurements in solutions and turbid suspensions. Measurements of a standard were identical when a spectrophotometer equipped with the probe was used or when a spectrophotometer was used in a conventional manner. The probe was calibrated for turbidimetric measurements with microorganisms by relating the apparent absorbancy measured on the spectrophotometer to the dry weight of each species of organism. Continuous measurements were made of the turbidity of growing cultures of Escherichia coli, Streptococcus mutans, and Saccharomyces cerevisiae. Transient changes in cell mass were observed in some cultures during continuous monitoring of growth. The data were recovered in a manner which allowed direct computer processing.